2001
DOI: 10.1097/00126097-200112000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Early morning surge in blood pressure

Abstract: Early-morning blood pressure is generally viewed as an important therapeutic target, for two reasons. First, for antihypertensive agents taken once daily in the morning, the timing of the trough plasma drug level, and thereby the lowest pharmacodynamic effect, often coincides with the early morning rise in blood pressure and heart rate. Evidence has been accumulated to suggest that blood pressure control throughout the 24 h period may be necessary to gain complete benefit from antihypertensive medication. In f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 29 publications
0
38
0
3
Order By: Relevance
“…This means that minimal drug levels, and hence the pharmacodynamic trough effect, coincide with the early morning surge in blood pressure. 26 Blood pressure control throughout the 24-h period is important to gain complete benefit from antihypertensive therapy. The Study on Ambulatory Monitoring of blood Pressure and Lisinopril Evaluation (SAMPLE) showed that LVH regression was predicted much more closely by treatment-induced changes in ambulatory blood pressure, which provide a measure of antihypertensive activity throughout the dosing interval, than clinic blood pressure, which indicates the extent of blood pressure control at an isolated time point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that minimal drug levels, and hence the pharmacodynamic trough effect, coincide with the early morning surge in blood pressure. 26 Blood pressure control throughout the 24-h period is important to gain complete benefit from antihypertensive therapy. The Study on Ambulatory Monitoring of blood Pressure and Lisinopril Evaluation (SAMPLE) showed that LVH regression was predicted much more closely by treatment-induced changes in ambulatory blood pressure, which provide a measure of antihypertensive activity throughout the dosing interval, than clinic blood pressure, which indicates the extent of blood pressure control at an isolated time point.…”
Section: Discussionmentioning
confidence: 99%
“…The Study on Ambulatory Monitoring of blood Pressure and Lisinopril Evaluation (SAMPLE) showed that LVH regression was predicted much more closely by treatment-induced changes in ambulatory blood pressure, which provide a measure of antihypertensive activity throughout the dosing interval, than clinic blood pressure, which indicates the extent of blood pressure control at an isolated time point. 27 The morning is also the time of the day when the risk of cardiovascular events is at its highest, 26 hence, the importance of the control of blood pressure at this time to prevent target-organ damage and reduce cardiovascular morbidity. The present study established the superiority of telmisartan in the control of blood pressure at the end of the dosing interval.…”
Section: Discussionmentioning
confidence: 99%
“…There is a marked diurnal variation in the onset of cardiovascular events, with a peak incidence of myocardial infarction, sudden cardiac death, and ischemic and hemorrhagic stroke occurring in the morning (6 AM to noon) (4)(5)(6)(7)(8)(9)(10)(11). In particular, 3-h after waking is the highest risk period of the day or night (6).…”
Section: Morning Hypertension: the Strongest Independent Risk Factor mentioning
confidence: 99%
“…This suggests that some pathogenic mechanism related to morning BP is more closely associated with stroke risk than the total vascular BP overload throughout the 24-h period. In the morning, a number of conditions, such as platelet hyperactivity, impaired fibrinolytic activity, and increased vasoconstriction, which are potential risk factors for triggering cardiovascular events, are aggregated (4,(8)(9)(10)(11)(18)(19)(20)(21)(22)(23)(24), and when coupled with the increased shear stress on the atherosclerotic vascular wall resulting from the morning BP surge, might trigger stroke events. Both morning BP level and morning BP surge in the Cox regression model were significantly associated with stroke risks.…”
Section: Morning Bp Levels and Stroke Incidencementioning
confidence: 99%
“…CARDIOVASCULAR events occur most frequently in the morning 1,2) especially within 3 hours after waking.…”
mentioning
confidence: 99%